The Interpretation of Luke 17:15 – 16 on the Concept of Gratitude in the Light of Ika Diocesan Anglican Communion - Okoh, Blessing Uenosen; Enuwosa, J. (NIU Journal of Humanities, 2023)
The Concept of Gratitude is compelling and facilitates the acknowledgement of human connection to the rest of humanity. It recognizes other people’s roles in life. Gratitude results to an active recognition of interdependence of one another. It is one of the most powerful feelings God has given to mankind the capacity to experience. It is essentially about not taking things for granted. The attitude of expressing Gratitude to people for kind gestures, contributions or roles enjoyed from a benefactor is an attribute highly prized by Jesus Christ as exemplified when he met and healed ten lepers who approached him to have mercy on them. Jesus commanded them to go and show themselves for the priests to examine them. On their way, they were cleansed of their leprosy. While others went their way, only one returned and he was a Samaritan. He came back praising and thanking God showing gratitude for the gesture. In total disappointment at the act of the nine other lepers, Jesus asked about them. He expected them to express Gratitude to God. By this act, Jesus frowned at the ingratitude and emphasized the importance of expressing Gratitude as displayed by the Samaritan leper who was blessed with complete wholeness of body and soul. He was described as a man of faith. This Paper is mainly aimed to examine the Concept of Gratitude and its Interpretation as expressed in Luke 17:15 – 16 and constructing a model for expression of Gratitude in Ika Diocesan Anglican Communion. Exegetical, hermeneutical, historical and phenomenological methods were employed to achieve the objective. The study therefore concludes that Gratitude is a moral cardinal virtue in the teaching of Jesus. Keywords: Interpretation, Concept, Gratitude, Anglican, Communion, Luke,